Respuesta :
Answer:
-1.5
Step-by-step explanation:
- 2 (y-2) = 4y + 8 - 2 (-4y - 3)
- 2y-4=4y+8+8y+6
- 2y-4=12y+14
- -4-14=14y-2y
- -18=12y
- y=-18/12
- y=-1.5
Answer:
Let's solve your equation step-by-step.
2(y−2)=4y+8−2(−4y−3)
Step 1: Simplify both sides of the equation.
2(y−2)=4y+8−2(−4y−3)
(2)(y)+(2)(−2)=4y+8+(−2)(−4y)+(−2)(−3
(Distribute)
2y+−4=4y+8+8y+6
2y−4=(4y+8y)+(8+6)(Combine Like Terms)
2y−4=12y+14
2y−4=12y+14
Step 2: Subtract 12y from both sides.
2y−4−12y=12y+14−12y
−10y−4=14
Step 3: Add 4 to both sides.
−10y−4+4=14+4
−10y=18
Step 4: Divide both sides by -10.
-10y/-10= 18/-10
Answer = y= -9/5
Step-by-step explanation:
BRAINLIEST PLEASE